PECULIARITIES OF FORMATION OF THE STATE POLICY OF BALANCED AGRICULTURAL LAND USE (INNOVATIVE ECONOMY, 2020)
Sydoruk B.O. PECULIARITIES OF FORMATION OF THE STATE POLICY OF BALANCED AGRICULTURAL LAND USEPurpose. The aim of the article is the scientific substantiation of the main components of the state policy of balanced use of agricultural land.Methodology of research. The research used the following methods of scientific research: monographic, compilation, analysis and synthesis, induction and deduction – for: transfer of knowledge of certain facts to general knowledge and vice versa; causal relationships of economic events and processes in the agrarian sector of the economy depending on the directions of land use, which in the complex provide in their unity the scientific substantiation of the problem of formation of the state policy of balanced use of agricultural land in the multilateral dialectical connection.Findings. The main components of the state policy of balanced use of agricultural land are determined. The stages of formation of the national and regional policy of balanced agricultural land use are substantiated. Conclusions are made on the necessity of the implementation of the state policy of balanced land use on the principles of decentralization of management activities in order to reconcile the interests of different categories of land users and ensure maximum ecological and economic and social efficiency of agricultural land use.Originality. The author’s approach to the process of coordinating interests in the field of agricultural land use at the local level is substantiatedPractical value. The results of the study are aimed at improving the process of formation of a national policy of balanced agricultural land use, which involves the following stages: the conceptual provision of balanced land use; the establishment of strategic priorities in the field of agricultural land use; planning of land use at different levels of management; the development and implementation of land management projects at the level agrarian formations.Key words: agrarian formation; balanced land use; land policy; land resources; land management; regional level; agricultural land use.
Keywords: Key words; agrarian formation; balanced land use; land policy; land resources; land management; regional level; agricultural land use.